Apocarotenoids Involved in Plant Development and Stress Response - Felemban, Abrar; Braguy, Justine; Zurbriggen, Matias D.; Al-Babili, Salim (Frontiers in Plant Science, 2019)
Carotenoids are isoprenoid pigments synthesized by all photosynthetic organisms and many heterotrophic microorganisms. They are equipped with a conjugated double bond system that builds the basis for their role in harvesting light energy and in protecting the cell from photooxidation. In addition, the carotenoids polyene makes them susceptible to oxidative cleavage, yielding carbonyl products called apocarotenoids. This oxidation can be catalyzed by carotenoid cleavage dioxygenases (CCDs) or triggered non-enzymatically by reactive oxygen species (ROS). The group of plant apocarotenoids includes important phytohormones, such as abscisic acid (ABA) and strigolactones (SLs), and signaling molecules, such as -cyclocitral. ABA is a key regulator of plant’s response to abiotic stress and is involved in different developmental processes, such as seed dormancy. SL is a main regulator of plant architecture and an important signaling molecule in the plant-rhizosphere communication. β-cyclocitral, a volatile derived from β-carotene oxidation, mediates the response of cells to singlet oxygen stress. Besides these well-known examples, recent research unraveled novel apocarotenoid growth regulators and suggests the presence of yet unidentified ones. In this review, we describe the biosynthesis and biological functions of established regulatory apocarotenoids and touch on the recently identified anchorene and zaxinone, with emphasis on their role in plant growth, development and stress response.